It's not all about autism: The emerging landscape of anti-vaccination sentiment on Facebook. Issue 16 (10th April 2019) - Hoffman, Beth L.; Felter, Elizabeth M.; Chu, Kar-Hai; Shensa, Ariel; Hermann, Chad; Wolynn, Todd; Williams, Daria; Primack, Brian A.
Highlights: Insight on individuals from Facebook profiles posting anti-vaccination content. Social media facilitates anti-vaccination connections and organization. Anti-vaccination posts on individual profile pages often skew risk perception. People and topics cluster in sub-groups—trust, alternatives, safety, and conspiracy. Anti-vaccination arguments are varied; need for targeted interventions. Abstract: Background: Due in part to declining vaccination rates, in 2018 over 20 states reported at least one case of measles, and over 40, 000 cases were confirmed in Europe. Anti-vaccine posts on social media may be facilitating anti-vaccination behaviour. This study aimed to systematically characterize (1) individuals known to publicly post anti-vaccination content on Facebook, (2) the information they convey, and (3) the spread of this content. Methods: Our data set consisted of 197 individuals who posted anti-vaccination comments in response to a message promoting vaccination. We systematically analysed publicly-available content using quantitative coding, descriptive analysis, social network analysis, and an in-depth qualitative assessment. The final codebook consisted of 26 codes; Cohen's κ ranged 0.71–1.0 after double-coding. Results: The majority (89%) of individuals identified as female. Among 136 individuals who divulged their location, 36 states and 8 other countries were represented. In a 2-mode network of individuals and topics, modularity analysis revealed 4 distinct sub-groups labelled as "trust, " "alternatives, " "safety, " and "conspiracy." For example, a comment representative of "conspiracy" is that poliovirus does not exist and that pesticides caused clinical symptoms of polio. An example from the "alternatives" sub-group is that eating yogurt cures human papillomavirus. Deeper qualitative analysis of all 197 individuals' profiles found that these individuals also tended to post material against other health-related practices such as water fluoridation and circumcision. Conclusions: Social media outlets may facilitate anti-vaccination connections and organization by facilitating the diffusion of centuries old arguments and techniques. Arguments against vaccination are diverse but remain consistent within sub-groups of individuals. It would be valuable for health professionals to leverage social networks to deliver more effective, targeted messages to different constituencies.